PENGARUH LOYALITAS KERJA, KOMUNIKASI KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PERUSAHAAN PT. GRESIK CIPTA SEJAHTERA - Muhammad Vaival Abidin; Heru Baskoro (Politeknik Negeri Ambon, 2025)
Intriduction: Company performance has not yet reached optimal levels without full support from employees. This incident at PT. Gresik Cipta Sejahtera which has not been maximal in increasing optimal performance. Based on the results of the pre-survey, it was found that permanent employees of PT. Gresik Cipta Sejahtera still does not understand the procedures given by superiors and there are deficiencies in communication between employees. This research aims to determine the influence of work loyalty, work communication, and work motivation on the performance of the PT company. Gresik Cipta Sejahtera. Among the factors that influence performance include work loyalty, work communication and work motivation. Methods: In this research method, primary data and secondary data obtained in the field and in literature, the research sample consists of 105 permanent employees at PT. Gresik Cipta Sejahtera uses the population method. Quantitative type of research using multiple linear regression analysis techniques assisted by IBM SPSS Statistics 26. Results: The research results show that the significant value of work loyalty, work communication, work motivation is (0.030.0.020.0.005) with the conclusion that work loyalty, work communication. Work motivation has a positive and significant effect on PT performance. Gresik Cipta Sejahtera The research results show that work loyalty, work communication and work motivation have a positive and significant effect on the performance of PT employees. Gresik Cipta Sejahtera. Employees who are loyal, able to communicate effectively, and have high motivation tend to show better and more productive performance. Keyword: loyalty, communication, motivation, employee performance